Study on single phase induction motor conditions using voltage level method / Mohd Safuan Ali Aspar - Ali Aspar, Mohd Safuan (2010)
The aim of the study was to analyze the performance of single phase induction motor (SPIM) by varying the duty cycle of buck chopper. The thesis also aims to study the behavior of SPIM characteristics under variable motor conditions. The chopper also has been used to control the voltage input for the single phase isolated gate bipolar transistor (IGBT) bridge inverter. The inverter used pulse-width modulation (PWM) technique to supply the motor. The work was conducted by using a digital computer simulation (MATLAB software).